Categorized and individualized behavioral phenotyping approaches for control and triple-hit schizophrenia-like model rats in acute and chronic reward-based systems: A pilot study - Zsofia Hernadi; Laszlo Kormoczi; Leatitia G. Adlan; Gabriella Kekesi; Alexandra Büki; Peter Liszli; Laszlo G. Nyúl; Gábor Braunitzer; Gyongyi Horvath (PLoS ONE, 2025)
A wide variety of acute test procedures are used for the behavioral characterization of schizophrenia rodent models, but prolonged observation in home-cage systems remains underexplored. This study aimed to profile the behavior of control (Wistar) and triple-hit schizophrenia-like (Wisket) model rats under two reward-based test conditions: the acute Ambitus test, a simple reward-collection task, and the delay-discounting paradigm in the HomeManner system, designed for extended observation periods. Wisket rats exhibited significant behavioral impairments compared to Wistar rats in the Ambitus test. However, in the HomeManner system, no significant group differences were observed at the cohort level due to heterogeneous individual behavioral patterns. Specifically, only half of the rats explored both food-providing trays, while others focused on one or ignored both. Subgroup analysis, based on tray activity patterns, revealed that Wisket rats displayed impaired cognitive processes and greater intolerance to delayed food rewards. Furthermore, personalized analysis indicated lower behavioral variability within the Wisket group compared to controls. The absence of a strong correlation between performance in the Ambitus and HomeManner tests suggests that these assessments capture distinct behavioral characteristics. This pilot study provides an extended behavioral phenotyping of rat substrains under both acute and chronic conditions. The automated HomeManner system demonstrates potential as a valuable tool for prolonged behavioral assessments. Importantly, this study underscores the value of categorized and personalized analyses in revealing behavioral differences that may not be apparent in group-level comparisons, thereby enhancing the translational relevance of preclinical research.